Modes of delivery of genetic testing services and the uptake of cancer risk management strategies in BRCA1 and BRCA2 carriers. (21st March 2013) - Pal, T; Lee, J‐H; Besharat, A; Thompson, Z; Monteiro, ANA; Phelan, C; Lancaster, JM; Metcalfe, K; Sellers, TA; Vadaparampil, S; Narod, SA
<x xml:space="preserve">Abstract</x> BRCA testing services are now offered by various healthcare providers, thus it is important to evaluate whether the implementation of cancer risk management (CRM) strategies varies by service provider. Using a registry‐based sample of 795 female BRCA mutation carriers, we explored the association between uptake of CRM strategies with duration of genetic counseling (GC) sessions, provider type, and other demographic and clinical variables. All participants completed a baseline questionnaire. Information about uptake of CRM strategies was collected for a subset of 438 participants who completed additional questions. Summary statistics and Pearson chi‐squared analysis were used to examine the associations between demographic and clinical variables with service delivery factors and with the uptake of various CRM strategies. Overall uptake of CRM strategies was high across all provider types. However, GC sessions were longer when provided by a genetics professional than by another provider (p < 0.001). Furthermore, higher frequencies of uptake of most CRM strategies were associated with longer GC sessions and when testing was performed by a genetics professional. Identification of factors to optimize delivery of these specialized GC services is important to maximize implementation of CRM strategies in BRCA carriers.